Clinical Analysis of Risk Factors for Mortality in Type A Acute Aortic Dissection: A Single Study From China - Yuan, Hongliang; Sun, Zhenxing; Zhang, Yongxing; Wu, Wenqian; Liu, Manwei; Yang, Yali; Wang, Jing; Lv, Qing; Zhang, Li; Li, Yuman; Xie, Mingxing (Frontiers in Cardiovascular Medicine, 2021)
Objective: Acute type A aortic dissection (ATAAD) is a fatal condition that requires emergency surgery. The aim of the present study was to determine pre- and intra-operative risk factors for in-hospital mortality in patients with ATAAD. Methods: Consecutive 313 patients with ATAAD who underwent emergency surgery at our hospital from February 2012 to February 2017 were enrolled in our study. Univariate and multivariate logistic regression analysis were performed to identify the pre-operative and intra-operative risk factors for in-hospital mortality. Results: Of the 313 patients, 32 patients (10.2%) died. Compared with survivors, non-survivors had higher heart rate, serum potassium level and EuroSCORE II, and higher incidence of moderate to severe pericardial effusion, supra-aortic vessels involvement, myocardial ischemia and lower-extremity ischemia. As for surgery-related factors, the duration of surgery and cardiopulmonary bypass time were longer in non-survivors than survivors. In addition, non-survivors were more likely to undergo coronary-artery bypass graft compared with survivors. On multivariate analysis, elevated plasma potassium level (OR: 43.0, 95% CI: 3.8–51.5, p < 0.001), high incidence of supra-aortic vessels involvement (OR: 4.4, 95% CI: 1.5–7.0, p = 0.008) and lower-extremity ischemia (OR: 4.9, 95% CI: 1.6–6.9; p = 0.009), and longer duration of surgery (OR 6.0, 95% CI: 1.8–18.7, p = 0.000) and cardiopulmonary bypass time (OR: 3.7, 95% CI: 1.3–9.3, p = 0.001) were independently predictive of higher mortality in patients with ATAAD. Conclusions: Supra-aortic vessels involvement, lower-extremity ischemia and elevated plasma potassium level are independent predictors of mortality in patients with ATAAD. A significant decrease in duration of surgery and cardiopulmonary bypass time is helpful to improve survival of patients.